2013
DOI: 10.1097/pai.0b013e3182632ff5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between HER2 Determined by Fluorescence In Situ Hybridization and Reverse Transcription-Polymerase Chain Reaction of the Oncotype DX Test

Abstract: The human epidermal growth factor receptor 2 (HER2) gene is amplified and its protein product overexpressed in about 20% of invasive breast cancers. Despite more than a decade of efforts to standardize HER2 testing, controversy persists regarding the most optimal testing method. Recently, Oncotype DX reports have begun including HER2 results in addition to the previously reported Recurrence Score. We compared HER2 results obtained by fluorescence in situ hybridization (FISH) in our laboratories with HER2 resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
0
18
1
Order By: Relevance
“…Analysis of HER2 results comparing FISH and Oncotype DX revealed a very high concordance of 97.2%. High concordance rates (96–98%) have been published . A closer subset examination demonstrates a striking difference between the two assays.…”
Section: Discussionmentioning
confidence: 94%
“…Analysis of HER2 results comparing FISH and Oncotype DX revealed a very high concordance of 97.2%. High concordance rates (96–98%) have been published . A closer subset examination demonstrates a striking difference between the two assays.…”
Section: Discussionmentioning
confidence: 94%
“…Discrepancies may arise due to subjective interpretation of IHC and FISH results, arbitrary cut-off levels for positive results that may differ between the commercial kits, or due to a low percentage of invasive tumour in the tissue block when performing RT-PCR. [7,8] Our pathologysupported genetic testing strategy enables the evaluation of a combination of tests most likely to overcome the limitations of a single test procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-gene expression tests that are based on real-time polymerase chain reaction (RT-PCR) methodology, such as Oncotype Dx, have been criticised for lack of reproducibility in determination of HER2 overexpression, which forms an integral part of the recurrence score. [7,8] MammaPrint is the only test cleared by the US Food and Drug Administration (FDA), and this independent confirmation of analytical and clinical validation provides a high level of confidence in test performance.…”
mentioning
confidence: 99%
“…It has been suggested that HER2 status can be assessed with different approaches as a continuous variable and can be assessed on mRNA level [19]. HER2 gene amplification determined with FISH is strongly associated with elevated mRNA and protein levels and small studies have reported on the concordance of HER2 status by RT-PCR to that by IHC and FISH [20]–[22]; Two independent studies have reported on the concordance between HER2 Quantitative Reverse Transcription Polymerase Chain Reaction (qRT-PCR) of the Oncotype Dx Test and the FDA-approved IHC/FISH assays and have yielded conflicting results [23], [24]. In the first study, a greater than 50% false-negative rate for Onco type DX RT-PCR for HER2 assessment was reported.…”
Section: Introductionmentioning
confidence: 99%